Correlation Between Principals’ Job Satisfaction and Their Normative Commitment - Harini, Hegar; Terminanto, Ade Ananto; Perkasa, Didin Hikmah; Pandaryasi, Henny; Brahma, Ismail Akbar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
The study aims to examine the influence of job satisfaction on public senior high school principals' normative commitment. A quantitative approach with a descriptive survey was adopted. The data were collected through questionnaires. A simple random sampling technique was employed. Ninety principals in the Jakarta Capital City region were involved as participants in the research. The data obtained were analyzed using correlation and path analysis. The result showed that job satisfaction has a direct positive influence on the principals' normative commitment. Additionally, the research signified that job satisfaction's extrinsic factors are more dominating than intrinsic factors. While the indicator too, has the most impact on the principals' normative commitment is a conviction to stay in the organization. Education authorities and policymakers are urged to promote the realization of factors influencing satisfaction to enhance principals' commitment and performance.